EFFECT OF CALCIUM SUPPLEMENTATION ON GIANT FRESHWATER PRAWN (Macrobrachium rosenbergii) MOULTING AND EGG QUALITY - Ikhsan Khasani; Narita Syawalia Ridzwan; Clive Jones (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2012)
A breeding program for giant freshwater prawn has been developed in Indonesia to supply good quality prawn seed to industry. To achieve the goal of the program, optimum conditions of both environment and nutrition must be provided. Calcium is the main compound of the prawn carapace, influencing moulting processes, especially during the premating moult. The effect of calcium supplementation in the prawn feed on moulting process and egg quality of giant freshwater prawn, Macrobrachium rosenbergii, was investigated. Experimental units consisted of 300 L plastic tanks stocked with 4 adult prawns comprising 3 female and 1 male. A standard prawn feed containing 30.39% crude protein; 0.82% Ca and 0.47% P was used as the experimental diet. A complete randomized design was‘applied in the study with 5 dosage levels of dicalcium phosphate i.e. 0%, 2%, 4%, 6%, and 8% with 4 replicates. Prawns were reared over 45 days. There were significant differences (P<0.05) in premoult, moult, and egg hatching rate, while no significant differences in intermoult or fecundity were observed (P>0.05). Egg hatching rate increased liniearly from 26.5%±9.9% to 50.8%±10.3% as calcium dosage increased from 0% to 8%. The number of eggs per spawn was not significantly different (P>0.05), ranging from 40,096 to 46,131 for females weighing 30.19 to 32.94 g. The results of this study suggest that giant freshwater prawns require dietary calcium supplementation to support moulting process and egg quality when reared in soft water.